The Relationship between Family Support and Maternal Readiness with Anxiety Levels Before Delivery - Ritonga, Dewi; Basyir, Vaulinne; Rasyid, Rosfita (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2025)
Anxiety in pregnant women is a common emotional condition that occurs during pregnancy, characterized by excessive feelings of anxiety, worry, or fear. Pregnancy anxiety itself is experienced by many pregnant women due to lack of knowledge, readiness and support from family, community and environment. Excessive anxiety during pregnancy can lead to an increased incidence of uterine atony, infection, maternal fatigue, and shock, while in infants it can increase the risk of preterm birth and low birth weight (LBW). This study aims to examine the relationship between family support and maternal readiness with the anxiety level of pregnant women before delivery. This study used a quantitative research design with a cross-sectional approach, conducted in the working area of Andalas Padang Community Health Center. The sample consisted of 59 third-trimester pregnant women, selected through Simple Random sampling. Data collection was carried out using a questionnaire. The results of this study showed that the percentage of pregnant women who received family support and experienced less severe anxiety was 52.2% (p=0.048), including analysis of this data using the Chi-Square Test. Furthermore, it was found that pregnant women who were less prepared for childbirth experienced severe anxiety at a rate of 50.0% (p=0.002). In conclusion, there is a relationship between family support and maternal readiness with anxiety levels before delivery in the working area of Andalas Padang Community Health Center.